Therapeutic Plasmapheresis: a revision of literature. - Claudia Altobelli; Pietro Anastasio; Alessandro Cerrone; Elisabetta Signoriello; Giacomo Lus; Corrado Pluvio; Alessandra F Perna; Giovambattista Capasso; Mariadelina Simeoni; Giovanna Capolongo (Karger Publishers, 2022)
Background: Therapeutic Plasmapheresis (TP) is an extracorporeal therapy that allows the removal of pathogens from plasma. The role of TP in immuno-mediated diseases and toxic conditions has been of interest for decades. Summary: We reviewed the recent literature on the application and the optimal choice of TP technique ranging from Plasma Exchange, Double Filtration Plasmapheresis, Rheopheresis, Immunoadsorptions and Lipidoapheresis. In addition, we report our experience in the application of TP for various diseases ranging in different medical specialties, following the American Society for Apheresis (ASFA) recommendations. Key Messages: Overall patients receiving TP showed an improvement in clinical and laboratory parameters. Our review and single center experience suggest a benefit of the application of TP in multiple clinical disciplines.